1990
DOI: 10.1149/1.2086266
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Stress in Ni, NiFe , CoFe , and CoNi Layers Measured by the Bent Strip Method

Abstract: The physical meaning and formulas for the calculation of the different, but interrelated, types of the internal stress (IS) in thin films (instantaneous, residual, and average) are reviewed. These formulas are then applied to the cases of plated Ni and NiFe, CoFe, and CoNi alloys. The IS profiles (the IS distribution through the film thickness) are given for all cases. The relationship between the IS and the structure parameter (phase composite, crystallite size, and microstain) changes with alloy composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…19 In any case hexagonal close packed ͑hcp͒ structure was observed, contrary to what occurs from other plating baths. 20,21 Therefore, the chloride bath tested allows us preparation of homogeneous Co-Ni coatings of selected cobalt percentage depending on the plating conditions.…”
Section: Resultsmentioning
confidence: 99%
“…19 In any case hexagonal close packed ͑hcp͒ structure was observed, contrary to what occurs from other plating baths. 20,21 Therefore, the chloride bath tested allows us preparation of homogeneous Co-Ni coatings of selected cobalt percentage depending on the plating conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Tensile stress is very common in electrodeposits [18][19][20][21] and cannot be due to the thermal expansion mismatch between the deposit and the substrate, because the electrodeposition is carried out at low temperatures. In some cases it is suggested that this intrinsic stress arises from the nonequilibrium growth during the electrodeposition or to the inclusion of additives or reaction products thereof in the deposit.…”
Section: Resultsmentioning
confidence: 99%
“…In single-beam laser deflectometry, a laser beam is reflected from the substrate and curvature changes are obtained by monitoring the position of the reflected spot. [1][2][3][4][5][6][7][8][9]14,15 Since stress resolution scales with the square of the substrate thickness, sputtered metallic layers on thin inert wafers are frequently used as samples to maximize resolution. 16, 17 Floro and Chason developed an improved version of this technique that relies on monitoring the deflection of an array of equally spaced laser beams reflected from the substrate to measure all components of in-plane substrate curvature with high resolution and robustness.…”
mentioning
confidence: 99%